Efficient synthesis of monophosphoryl lipid A mimetic RC-529. Issue 7 (22nd November 2021) - Zhou, Chengkai; Xu, Zhuojia; Li, Gen; Gao, Qi; Sui, Qiang; Li, Tiehai
Abstract: An efficient approach for the facile synthesis of a potent vaccine adjuvant RC-529 is described. The synthetic strategy relies on the flexible use of orthogonal protecting groups, which makes it possible to accomplish selective phosphorylation, glycosylation and acylation, respectively. In addition, the use of readily cleaved 2-naphthylmethyl (Nap) ether and allyl esters as permanent protecting groups greatly facilitates the final global deprotection steps to obtain pure RC-529. This work will contribute to the synthesis of lipid A and its derivatives. Graphical Abstract: UF0001